Writing Majors : Eighteen Program Profiles - Giberson, Greg; Nugent, Jim; Ostergaard, Lori (Book collections on Project MUSE., 2014)
The writing major is among the most exciting scenes in the evolving American university. Writing Majors is a collection of firsthand descriptions of the origins, growth, and transformations of eighteen different programs. The chapters provide useful administrative insight, benchmark information, and even inspiration for new curricular configurations from a range of institutions. A practical sourcebook for those who are building, revising, or administering their own writing majors, this volume also serves as a historical archive of a particular instance of growth and transformation in American.